Senescence drives non-cell autonomous tumorigenesis in the pituitary gland - Jose Mario Gonzalez-Meljem; Juan Pedro Martinez-Barbera (Molecular & Cellular Oncology, 2018)
Novel detrimental functions of senescent cells have been recently uncovered in the context of cancer development and progression, which they mainly exert through the secretion of several pro-tumorigenic factors. Here we discuss how cellular senescence and its secretory phenotype can be involved in the widely unexplored phenomenon of paracrine tumorigenesis.